IMPROVING MENTAL WELL-BEING: THE IMPACT OF PILATES AND DEEP BREATHING ON HYPOCHONDRIASIS AMONG COLLEGE STUDENTS - Paulraj Manickavelu; Babu Subbiah; Santhiya Panneerselvam; Anand Babu Kaliyaperumal; Lakshna Girija Baskaran (The Indonesian Journal of Public Health, 2026)
Introduction: Health anxiety, also known as hypochondriasis, is prevalent among college students and leads to significant worry and sadness. A study has reported that 3.28% of medical students face this problem. In addition, a survey from South India has documented that 11% are affected. Exercise and mindfulness may help reduce this issue. Aims: This study aimed to reduce the anxiety and hopelessness associated with hypochondriasis among college students via Pilates and deep-breathing practice. Methods: The design was quasi-experimental, with pre- and post-assessments to evaluate how deep-breathing exercises and Pilates might affect anxiety and depression. Convenience sampling was used, and 15 college students aged 18–25 years were included. The Hospital Anxiety and Depression Scale was employed to determine the levels of anxiety and depression at the start and end of the 6-week program. Results: Analysis using a paired t-test showed that both anxiety and depression decreased significantly after the session. Anxiety declined from a mean of 16.06 to 7.066 (t = 21.73, P < 0.001), and depression from 11.33 to 5.733 (t = 9.72, P < 0.001). These results indicate that the treatments alleviate the symptoms, allowing the patients to relax. Conclusion: The findings establish that college students with hypochondriasis benefit from diaphragmatic breathing and Pilates. These mental health interventions will enhance coping and reduce depression and anxiety, among other benefits, thereby improving overall health resilience.